2020
DOI: 10.1016/j.cej.2019.123412
|View full text |Cite
|
Sign up to set email alerts
|

A new formulation for symbolic regression to identify physico-chemical laws from experimental data

Abstract: A modification to the mixed-integer nonlinear programming (MINLP) formulation for symbolic regression was proposed with the aim of identification of physical models from noisy experimental data. In the proposed formulation, a binary tree in which equations are represented as directed, acyclic graphs, is fully constructed for a pre-defined number of layers. The introduced modification results in the reduction in the number of required binary variables and removal of redundancy due to possible symmetry of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
(59 reference statements)
0
32
0
Order By: Relevance
“…54,63 However, in all the presented solutions, temperature control is not ensured and, in some cases, mixing appears to be far from ideal, stressing the need for standard 48 and Houben et al 13 The most common adopted techniques for reactive systems are UPLC and HPLC, 10,49,53,[101][102][103][104][105][106][107][108][109][110][111][112][113] GC, 113,114 MS, 37,40,46,50,52,55,57,106,115 IR, 53,59,113,115,116 Raman, 53 and UV spectrophotometry. 114,117,118 However, according to the theoretical framework outlined by Bernardo et al, 41 For formulated liquid products, the main general desired properties can be identified as: stability, aspect (color and turbidity), viscosity, surface tension, pH, conductivity, zeta potential, and droplets size distribution, in the case of emulsions. Therefore, more complex, analytical sensors need to be identified and integrated in the robotic platforms to acquire data about different properties at the same time.…”
Section: Robotic Platformsmentioning
confidence: 99%
See 3 more Smart Citations
“…54,63 However, in all the presented solutions, temperature control is not ensured and, in some cases, mixing appears to be far from ideal, stressing the need for standard 48 and Houben et al 13 The most common adopted techniques for reactive systems are UPLC and HPLC, 10,49,53,[101][102][103][104][105][106][107][108][109][110][111][112][113] GC, 113,114 MS, 37,40,46,50,52,55,57,106,115 IR, 53,59,113,115,116 Raman, 53 and UV spectrophotometry. 114,117,118 However, according to the theoretical framework outlined by Bernardo et al, 41 For formulated liquid products, the main general desired properties can be identified as: stability, aspect (color and turbidity), viscosity, surface tension, pH, conductivity, zeta potential, and droplets size distribution, in the case of emulsions. Therefore, more complex, analytical sensors need to be identified and integrated in the robotic platforms to acquire data about different properties at the same time.…”
Section: Robotic Platformsmentioning
confidence: 99%
“…This approach has been successfully applied mainly for the identification of predictive kinetic models in the field of reaction engineering and chemical reaction development. 118 Moreover, the current state of art focused on the problems of model selection out of a library of pre-derived models [162][163][164][165] and parameter estimation, 163,166 recently been published, such as measurements of gas solubility in liquids. 167 Also, several pioneering works 55,61,168 have shown advances in both the hardware and the software for the exploration of physicscontrolled phenomena in microfluidics, for example, multiphase droplets generation.…”
Section: Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported by Neumann et al [32], several global solvers are available to deterministically solve non-convex MINLP problems. These solvers include ANTIGONE [33], BARON [34], Couenne [35], LINDO [36], and SCIP [37].…”
Section: Solution Algorithmmentioning
confidence: 99%